Analysis of Factors Affecting the Compliance Rate of Advertising Taxpayers in Pati Regency - Sinta Nuril Badriya; Adelina Citradewi (DIPONEGORO UNIVERSITY, 2026)
This study aims to analyze the influence of taxpayer awareness, tax outreach, the e-billing system, the quality of tax officials’ services, and tax penalties on the compliance rate of advertising taxpayers at the Pati Regency BPKAD. The level of compliance among advertising taxpayers remains a challenge for local tax authorities, affecting regional tax revenue collection. This study employs a quantitative method using primary data obtained through the distribution of questionnaires to advertising taxpayers. The sampling technique used purposive sampling with a total of 131 taxpayers as respondents. Data analysis was conducted using SPSS version 27 through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, F-tests, T-tests, and the coefficient of determination. The results of the study indicate that taxpayer awareness, tax outreach, and tax penalties do not have a significant effect on the level of compliance among advertising taxpayers. Meanwhile, the e-billing system and the quality of tax administration services have a positive and significant effect on the level of compliance among advertising taxpayers.